A study of clinical and laboratory profile of dengue fever in a tertiary care centre of Uttarakhand, India - Singh, Ragini; Singh, S. P.; Ahmad, Niaz (International Journal of Research in Medical Sciences, 2017)
Background: Dengue is an important cause of mortality and morbidity in India. Many recent studies have shown varied clinical manifestations from different geographical locations. There is paucity of data on this topic from this region. The present study was conducted to find out the clinical features, complications, response to treatment and outcome of patients suffering from dengue in a tertiary care centre of Uttarakhand, India. Methods: The study was performed at SGRR Institute of Medical & Health Sciences, Dehradun, which is a tertiary care hospital of Uttrakhand. The study period was of 1 year from July 2012 to June 2013. Patients of 12 years of age or above it who were antigen positive or antibody positive were included in the study. All such patients who were admitted in the hospital underwent detailed clinical examination and investigation. Results: Dengue infection was identified in 140 patients. Thrombocytopenia was the commonest hematological abnormality. Splenomegaly, hepatomegaly, and hepatosplenomegaly, were common findings. Renal, hepatic and cerebral dysfunctions were noted. Mortality was seen in 5 (3.6%) patients. Encephalitis, shock and ARDS were associated with high mortality and poor outcome. Conclusions: Dengue is an important cause of mortality and morbidity in Uttarakhand. High index of suspicion, early diagnosis, monitoring of the clinical and laboratory parameters and prompt intervention may help in reducing the mortality.